Adolescent perception of sexual and reproductive health rights and access to reproductive health information and services in Adaklu district of the Volta Region, Ghana - Desmond Klu; Margaret Gyapong; Percival Delali Agordoh; Charles Azagba; Evelyn Acquah; Phidelia Doegah; Anthony Ofosu; Evelyn Korkor Ansah (BMC, 2023)
Abstract Background One of the key targets of Ghana's Adolescent Health Service Policy and Strategy is to ensure that 90% of adolescents and young people have knowledge of sexual and reproductive health services and rights. This phenomenon has led to the establishment of adolescent-friendly health facilities to increase access to health information and services among adolescents. Despite these efforts, access to health information and service utilisation remains low among adolescents. Our study seeks to examine adolescents' perception of sexual and reproductive health rights (SRHR) and access to reproductive health information and services in the Adaklu district of the Volta region of Ghana. Methods A baseline cross-sectional household survey of 221 adolescents aged 10-19 years in 30 randomly selected communities was used. A structured questionnaire was developed and administered to the respondents. A binary logistic regression analysis was used to examine the association between adolescents' perception of adolescent sexual and reproductive health rights (ASRHR) and access to reproductive health information and services. Results Adolescents' perception of SRHR was poor, and this poor perception may have been reflected in a few proportions (10%) of adolescents accessing SRH information and services. Majority (91.9%) of adolescents do not use sexual and reproductive health (SRH) services in the Adaklu district. Adolescents who attained primary education (aOR = 5.99, CI: 1.16-30.95), those who never had sexual communication with their father (aOR = 8.89, CI: 1.99-39.60) and adolescents who never experienced any form of sexual coercion (aOR = 11.73, CI: 1.61-85.68) had a higher likelihood of not utilising SRH services in Adaklu district. Regarding access to SRH information, adolescents who ever discussed sexual matters with their fathers, those who ever used contraceptives and adolescents who ever experienced sexual coercion had lower odds of accessing information on contraception, sexually transmitted infections, and teenage pregnancy. Conclusions Access to and use of sexual and reproductive information and health services among adolescents in Adaklu district remain very low, which has implications for adolescents' knowledge and perception of their SRHR. Considering the factors predicting this phenomenon, it is recommended that interventions can be tailored to address the unique challenges faced by adolescent in accessing comprehensive SRH support.